COUNSELING MODEL BASED ON BACKWARD CHAINING OF STUDENT BEHAVIOR AT SMK 10 MUHAMMADIYAH KISARAN - Muhammad Amin; Boby Supriyanto; Muhammad Abyanda Tamaza; Ilham Asy’ari; Riszki Fadillah (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2023)
Student development includes conduct as a key component. Student behavior becomes crucial in deciding how successful students will be in different spheres of life. The variety of student behavior can hinder the learning process and personal development of students. Through the development of an expert system-based counseling model based on backward chaining, this study seeks to discover trends in student behavior. The research process starts with problem analysis, goal setting, literature study, data collection, system design and implementation, and results analysis. It then moves on to counseling model development and implementation in the school setting. To determine the reasons for the unruly behavior of the kids, data were analyzed using a backward chaining methodology. UML Usecase diagrams are used in system design to define the roles of actors and users. The established counseling model, which consists of 14 behaviors, 67 phenomena/symptoms, and 14 rules, focuses on goals and methods to modify student behavior. Three students underwent system testing based on previously achieved goals from therapy. The findings revealed "Smoking," "Emotional Problems," and "Fighting" among the student behaviors. When the Backward Chaining-based counseling model is used, it is simpler for homeroom teachers to gather information about students' conduct from them and to offer remedies based on the transfer of professional knowledge without having to wait for the counselor guidance procedure